Exploring Practitioners’ Lived Mathematical Play Practices in the Early Childhood Care and Education Setting - Okeke, Chinedu; Baloyi-Mothibeli, Seipati; Ugwuanyi, Christian (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
Attention to engaging children in math-related play is increasing, but it is not clear how early childhood practitioners in South Africa practice lived mathematical play. This study sought to determine early childhood care and education practitioners’ lived mathematical play practices. The study was anchored on Vygotsky's social constructivist theory, which holds that children learn best when they are scaffolded and mediated by people who have more knowledge than they do. The study adopted a phenomenological research design using a sample of 10 practitioners. The researchers gathered data using a semi-structured interview guide. A thematic analysis was used to analyze the data that were gathered. The findings of the study revealed that the lived mathematical play practices of early childhood partitioners include building relationships, showing respect, having passion, being experienced, and acting in loco parentis. Moreover, practitioners seem to know and understand what was expected of them in ECCE, particularly regarding the teaching of mathematical play-based learning. It was recommended that practitioners' lived mathematics play-based learning can be improved through appropriate teacher development programs and by gaining acceptable qualifications.